Pelatihan Desain Grafis Berbasis Android Guna Meningkatkan Kreativitas Remaja Desa Betek Mojoagung - Muhammad Farid Nasrulloh; Muhammad Ridhoi Asyari; Muhyiddin Zainul Arifin; Septian Ragil Anandita; Muhammad Ansori Aris (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Graphic design is a communication process that uses visual elements such as typography, photography and illustrations for the purpose of creating a perception of the message to be conveyed. Usually, graphic designers use images, photos, symbols, as well as various forms of language and other visual elements in their work. Visual communication like this often also involves the use of letters to complete the message you want to convey. The problems that need to be resolved regarding the planned community service activities are as follows: (1) Activities carried out by village teenagers experience obstacles that affect their productivity. (2) There is a shortage of teenagers who have the ability to use applications that can support their potential. (3) Frequent use of smartphones for social media and playing games has become common among teenagers. (4) Limitations in social interaction between teenagers are currently an important concern. The community service method uses the ABCD (Asset Based Community Development) approach, namely a method that utilizes assets owned by the local community which are seen to support community empowerment activities. The objectives to be achieved in implementing this activity are as follows: (1) Providing knowledge about graphic design to teenagers as part of their education. (2) Teaching the principles of coloring in the design process. (3) Encouraging changes in consumer behavior in the use of smartphones by teenagers. (4) Building and improving relationships between teenagers to make them closer and more sustainable.